Probing the CGM of low-redshift dwarf galaxies using FIRE simulations. Issue 1 (27th October 2020) - Li, Fei; Rahman, Mubdi; Murray, Norman; Hafen, Zachary; Faucher-Giguère, Claude-André; Stern, Jonathan; Hummels, Cameron B; Hopkins, Philip F; El-Badry, Kareem; Kereš, Dušan
ABSTRACT: Observations of ultraviolet (UV) metal absorption lines have provided insight into the structure and composition of the circumgalactic medium (CGM) around galaxies. We compare these observations with the low-redshift ( z ≤ 0.3) CGM around dwarf galaxies in high-resolution cosmological zoom-in runs in the FIRE-2 (Feedback In Realistic Environments) simulation suite. We select simulated galaxies that match the halo mass, stellar mass, and redshift of the observed samples. We produce absorption measurements using trident for UV transitions of C iv, O vi, Mg ii, and Si iii . The FIRE equivalent width (EW) distributions and covering fractions for the C iv ion are broadly consistent with observations inside 0.5 R vir, but are underpredicted for O vi, Mg ii, and Si iii . The absorption strengths of the ions in the CGM are moderately correlated with the masses and star formation activity of the galaxies. The correlation strengths increase with the ionization potential of the ions. The structure and composition of the gas from the simulations exhibit three zones around dwarf galaxies characterized by distinct ion column densities: the discy interstellar medium, the inner CGM (the wind-dominated regime), and the outer CGM (the IGM accretion-dominated regime). We find that the outer CGM in the simulations is nearly but not quite supported by thermal pressure, so it is not in hydrostatic equilibrium, resulting in halo-scale bulk inflow and outflow motions. The net gas inflow rates are comparable to the star formation rate of the galaxy, but the bulk inflow and outflow rates are greater by an order of magnitude, with velocities comparable to the virial velocity of the halo. These roughly virial velocities ( 100 km s^-1 ) produce large EWs in the simulations. This supports a picture for dwarf galaxies in which the dynamics of the CGM at large scales are coupled to the small-scale star formation activity near the centre of their haloes.